Estudo termodinâmico de hidrogéis superabsorventes - Raquel de Resende Janot Pacheco (2014)
In this work, a thermodynamic study of superabsorbent hydrogels was done, involving a broad review of theories and thermodynamic models concerning superabsorbent polymers, the development of a thermodynamic equation for these systems and the synthesis and characterization of gels based on acrylamide (AA) and sodium methacrylate (NMA) and, as crosslinkers, N,N’methylenebis(acrylamide) (MBA) and ethylene glycol dimethacrylate (EGMA). Ammonium Persulfate (APS) and N,N,N’,N’-Tetramethyl-ethylenediamine (TMEDA) were used for copolymerization reaction initiation and catalysis. The thermodynamic study pointed out to the importance of Flory-Rehner theory in order to understand the mixture term for hydrogels, complemented by Peppas theory, in the case of superabsorbent hydrogels, in which ionic term plays an important role on swelling equilibrium. It indicated also the importance of no elementary models for rubber elasticity, particularly the Phantom Network theory, for understanding the polymeric network thermodynamic response to swelling caused by polymer-solvent interaction. An equation was obtained to characterize hydrogels thermodynamic behavior at equilibrium, based on FloryRehner, Peppas and Phantom Network theories. Consistent hydrogels were obtained at the limit of sol/gel phase transition, with fixed concentrations of ionic monomer and crosslinker, of 30% and 1%, respectively (m/total monomer mass in %), for 6% of total monomer, in the case of MBA and 14%, for EGMA, demonstrating the different capacity of the crosslinkers used, on polymeric network formation. By varying the ionic monomer concentration, hydrogels with significant differences on swelling degree were obtained, for both crosslinkers, with a greater expansion for higher NMA concentration. However, this behavior presented fluctuations, with maximum peaks, fluctuations that were more pronounced for total monomer concentrations near phase transition. At this condition, near phase transition, swelling curves superposition showed the ionic monomer significant effect on hydrogels expansion. For total monomer concentrations near phase transition, hydrogels were obtained showing swelling degrees close to 400 g/g, for MBA, and 460 g/g, for EGMA, using 35% of ionic monomer concentration. By using light scattering technique, for hydrogels synthesized with any of the two crosslinkers, NMA concentration increase contributed to diminish hydrogels spatial inhomogeneities, as observed by the decrease of the hydrodynamic correlation length.